Antimicrobial and antioxcidant activities of Vitex negundo L. leaves - Zargar, Mohsen (2012)
This study was conducted to assess the biological activities of different extracts of Vitex negundo L. including antioxidant, antibacterial, antifungal and antiviral activity. In addition, profiling of bioactive compounds of the samples was also done. Antioxidant activity of essential oil, methanol and n-hexane extracts of V. negundo leaf were performed using 2,2-diphenyl-1-picrylhydrozyl (DPPH) free radical scavenging capacity, ferric ion reducing antioxidant power (FRAP) and β-carotene-linoleic acid assays. Results of the present study showed that methanol extract of V. negundo leaf exhibited significantly (p < 0.05) higher antioxidant activity than those of n-hexane extract and essential oil. The essential oil, methanol and n-hexane extracts of V. negundo leaf were also tested for antimicrobial activity against nineteen pathogenic bacteria and five pathogenic yeasts belonging to Candida family utilizing Agar disc diffusion,minimum inhibitory concentration (MIC) and minimum bactericidal/fungicidal concentration (MBC/MFC). The essential oil showed antibacterial activity against 16 of 19 tested bacteria with inhibition zone ranging from 7 to 15 mm. The higher inhibition zone diameter for essential oil was that of Vibrio cholera and Staphylococcus aureus (15 mm) followed by E. coli with 14 mm inhibition zone. The methanol extract exhibited strong antibacterial activity against Shigella dysenteriae with 18 mm inhibition zone and MIC value of 3.12 mg/mL followed by that of Vibrio cholerae and Klebsiella pneumoniae with inhibition zone 14 mm and MIC value 6.25 mg/mL, respectively. Generally, the n-hexane extract showed lower antibacterial activity compared to that of methanol extract. However, the methanol extract and essential oil did not show any activity against all Candida strains tested. On the other hand, the n-hexane extract showed weak activity against C. tropicalis and C.lusitaniae. Antiviral activity of essential oil, methanol and n-hexane extracts of V. negundo leaf was evaluated against respiratory syncytial virus (RSV) and herpes simplex virus type 1 (HSV-1). Antiviral activities assay were performed in both intracellular and extracellular antiviral method. Methanol extract showed intracellular antiviral activity against both RSV and HSV-1 with SI value of 10.2, On the other hand, essential oil of V. negundo leaf showed intracellular antiviral activity against RSV and HSV-1 with SI value of 4.92 and 4.6,respectively. The n-hexane extract showed no activity against both RSV and HSV-1in both intracellular and extracellular manner. Chemical compositions of essential oil, methanol and n-hexane extracts of V. negundo leaf were determined using gas chromatography–mass spectrometry (GC/MS). The results of the study showed that major constituents of methanol extract of V. negundo were identified as linoleic acid methyl ester (11.26%), alpha isomethyl ionone (10.27%), ledol (7.31%) and caryophyllene (4.13%), whereas the major constituents of that of n-hexane extract were tetracontane (22.98%), tetrapentacontane (21.42%), hexacontane (3.35%),hexatriacontane (2.61) and beta-Thujene (2.04%). Also, the results of the present study showed that the major constituent of essential oil of V. negundo leaf were identified as α—thujene (44.47%), α-terpinene (10.3%), ɣ-terpinene (4.78%), 4-terpinenyle acetate (3.56%) and citronellol (2.51%) was identified as major monoterpenes, and also,viridiflorene (4.13%), bisabolene (3.97%), citronellol (2.51%), viridiflorol (2.05%),caryophyllene (1.73%), and cadinol (1.17%) were identified as major sesquiterpenes. The results of this study showed that V. negundo extracts possess effective bioactive compounds with broad spectrum of activity against a panel of pathogenic bacteria that are responsible for infection diseases. Also of methanol extract of V. negundo has shown antiviral activities against RSV, whereas the essential oil showed antiviral activity against RSV and HSV-1. These biological properties could be due to bioactive compounds in this plant. This medicinal plant may represent new source of antimicrobial activity and probably explain the reason for the use of the plant by the locals in treating a number of infectious diseases.